Ghana - Assessment of Stage 1 : Use of Country Procurement Systems in Bank-Supported Operations - Proposed Piloting Program - World Bank (Washington, DC, 2013)
The present report comprises the findings of both missions conducted to complete stage one of the assessment. It is structured along the following lines. Chapter one presents a summary analysis of the overall Public Financial Management (PFM) environment in which Ghana's public procurement system operates as based on the existing External Review of Public Financial Management (ERPFM), Public Expenditure and Financial Accountability (PEFA) and other PFM reports. Chapter two summarizes previous assessments of status of reforms to public procurement in Ghana. This includes the country's Country Procurement Assessment Report (CPAR) with the status of its action plan, as well as the recommendations and actions taken based on the 2007 External Review of Public Financial Management (ERPFM) Joint Assessment of the national procurement system. Chapter three reviews the government's public procurement reform strategy. Chapter four presents the detailed findings of the country level procurement systems assessment, using the OECD-DAC (Organization for Economic Co-operation and Development-Development Assistance Committee) methodology for assessment of national procurement systems, that consists of a system of 4 pillars and 54 sub-indicators, and a scoring system of zero (0) to three (3). Chapter four concludes with a summary of scoring comparing the scores assessed to the minimum scores required as detailed in the document 'use of country procurement systems in Bank-supported operations: piloting program', released for disclosure on June 19, 2008. Chapter five presents a series of institutional strengthening and reform issues (action plan) required to achieve the mandatory scores needed to advance to the next stages for the piloting program. The action plan is broken down into issues, mitigation measures (actions), entity responsible, status of Government's comments, date to complete action, and cost estimated for action.